THE ROLE OF ARTIFICIAL INTELLIGENCE IN COMPUTER TECHNOLOGY (Modern education and development, 2025)
The rapid development of artificial intelligence (AI) has transformed various sectors, especially computer technologies, creating profound impacts on software, hardware, and computational systems. AI applications, such as machine learning, natural language processing, computer vision, and robotics, have revolutionized the way computers are used and have driven innovation in areas like data analysis, automation, and personalized experiences. This article explores the role of AI in modern computer technologies, highlights the key areas where it has made significant advancements, and discusses future prospects and challenges. The intersection of AI and computing holds the promise to continue shaping the technological landscape, offering new solutions to existing problems while presenting ethical and operational considerations.